Financing Higher Education in Africa - World Bank (World Bank, 2012)
This report demonstrated that the key for success in a globalized world lies increasingly in how effectively a country can assimilate the available knowledge and build comparative advantages in areas with good growth prospects and how it can use technology to address the most pressing environmental challenges. Higher-level institutions in Sub-Saharan Africa that is equipped to impart quality education and conduct relevant applied research can play a critical role in producing workers with the skills to assimilate technology and make effective decisions that help industry to diversify into a broader range of products. Good-quality and relevant higher education is also a key to stimulating innovations in new varieties of crops, new materials, or sources of energy that would facilitate progress toward reducing poverty, achieving food security, and improving health. This report is a follow-up to the 2008 study. It examines current practices in financing higher education in Sub-Saharan Africa, taking into account the significant differences that exist among countries. Drawing on experience from around the world, the report also examines the range of policy options that could be considered in tackling the financing issue. The report also carries an encouraging message. It shows that a full range of options do exist and that some African countries and institutions have started implementing them. Private higher education is experiencing spectacular growth in Africa. Cost-sharing programs are being implemented in many universities, accompanied by student loans and financial aid for low-income students. Higher education is being diversified to offer lower cost and more effective delivery alternatives. In a few cases, impressive reforms to improve internal efficiency have been implemented, and governments are increasingly adopting more effective budget management practices.